The W[ ]rth of Objects - Johnson, Charles (Auckland University of Technology, 2021)
This research focuses upon de-centering the notion of the ‘human’ from an ontological standpoint through the creative exploration and interrogation of found objects. Traditionally ‘non-human’ matter is viewed as passive and inert – this traditional humanist thinking has brought upon many of the global issues we face today. This research entails the creative investigation of a variety of objects that have presented themselves throughout the research. Creating artworks from these objects through varied technological systems allows these objects to speak for themselves, transcribing their agencies to a frequency we as humans can listen to and understand. The technological processes to do such have been guided by the physicality and hidden narratives of the objects themselves. Engaging with tough questions about the objects in our lifeworld and the agencies they possess is a crucial task, as they have an undeniable, devastating and haunting effect on us when ignored or left to be ‘passive and inert’.
Keywords: Object Oriented Ontology; Philosophical Posthumanism; New Materialism; OOO; Posthuman; Object; Objects; Agency; Vitality